2020
DOI: 10.1097/md.0000000000020303
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and cardiovascular risk and mortality

Abstract: Background: The role of dietary inflammatory index (DII) in cardiovascular disease (CVD) risk and mortality is still controversial. This systematic review and meta-analysis of cohort studies aimed to evaluate the effect of DII, indicating a pro-inflammatory diet, on the incidence and mortality of CVD. Methods: A comprehensive literature search of articles published through August 2019 was performed in Medline, EMBASE, and Web of Science. The pooled rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 43 publications
0
41
1
Order By: Relevance
“…Several studies have assessed the relationship between the inflammatory potential of diet and overweight or obesity. A higher DII score, indicating a more pro-inflammatory diet, has been associated with a higher BMI, waist circumference, waist-height ratio, and increased risk of cardiovascular diseases and cancer [ 15 , 28 , 29 , 30 ]. A cross-sectional study, in the Cohort of Universities of Minas Gerais, also displayed an increased prevalence of obesity with a higher DII score [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the relationship between the inflammatory potential of diet and overweight or obesity. A higher DII score, indicating a more pro-inflammatory diet, has been associated with a higher BMI, waist circumference, waist-height ratio, and increased risk of cardiovascular diseases and cancer [ 15 , 28 , 29 , 30 ]. A cross-sectional study, in the Cohort of Universities of Minas Gerais, also displayed an increased prevalence of obesity with a higher DII score [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…DII represents a unique biological mechanism underlying the diet–mental health link over other diet indices by capturing the inflammatory effect of diet. In addition, previous studies have demonstrated the predictive value of DII in chronic inflammatory disease, including obesity ( 44 ), cardiovascular disease ( 45 ), metabolic syndrome ( 46 ), and various types of cancers ( 47 ). All findings mentioned above indicate that the DII may potentially serve to be prevention targets of mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the 35 independent meta-analyses, which included 261 primary studies in 16 articles ( 9 , 24 38 ). These 16 articles were published between 2018 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine publications were excluded after full-text screening for different reasons (Figure 1 and Supplementary Table 2). The final selection yielded 16 articles to be included for analysis (9,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation